PRAKONSENTRASI DAN ANALISIS RENIK Hg (II) BERBASIS FLOW INJECTION ANALYSIS (FIA) - Nasra, Edi
Mercury is one of the most toxic heavy metal and one of the sources of pollutant for our environment. The existences of mercury can come from human activities, such as industrial waste. The toxicity of mercury increases drastically on transformation to its organic forms, such as methyl mercury via biomethylation through bacterial intervention in the environment. Mercury released into the atmosphere by a variety of natural and anthropogenic sources and can be easly enter human body through respiratory system or food. The accumulation of mercury on human body can cause so many dangerous impact such as cancer, reproduction gland disfunction, brain damage, osteophorosis, and nervous system poissoning. Therefore, the simple and effective analytical methods for determination of mercury are needed. Many experiments on mercury analysis have been reported, such as cold vapour atomic absorption CV-AAS, inductively coupled plasma mass spectrometry ICP-MS and several chromatographic techniques modificated with spectrometric methods. But yet, those methods have a complicated pretreatment and a highly cost. To increase the analitical sensitivity, some preconcentration methods, such as using solid phase extraction, hava been used to combine with AAS, AFS, ICP-MS or UV Visible Spectrometer based on Flow Injection Analysis (FIA) were effective for analysis of mercury. This method can be used for determination of very low concentration of mercury with a detection limit at part per billion level. The flow injection technique has such merits as a small volume of waste, which enhances the sensitivity of the methods and allows easy connection with an automated system. Preconcentration is a method to increase an analyte concentration without standard addition. In this research, column C-18 is used to preconcentration and analysis trace mercury based on association complex formation between HgI42- and Ferroin, Fe(phen)32+. C-18 is non polar sorbents may be used to collect metal complexes of low polarity from the aqueous phase by reversed phase adsorption. The association complexes are subsequently eluted by a suitable solvent such as methanol or ethanol. Results of the research show that HgI42-, ferroin and association complexes adsorbed at 352, 510 and 512 (? = 68,619 L mol- cm-) respectively, which indicated the sensitivity of procedure. The formation of an ion-association of HgI42- and ferroin